Kebebasan Berekspresi di Media Sosial: Dialektika Hak Asasi Manusia dan Hukum Islam dalam Pembentukan Regulasi Digital - Gufron Zainal Abidin Sdawi Manasiq; Mohsi Mohsi; Hammis Syafaq; Fahmi Assulthoni; Abd Ghani (Institut Agama Islam Miftahul Ulum Pamekasan, 2026)
The normative regulation of freedom of expression on social media platforms remains unresolved, particularly in Muslim-majority countries that simultaneously operate under international Human Rights (HR) frameworks and Islamic Law principles. Available comparative scholarship tends to address this issue in general terms, without examining its specific implications within digital ecosystems. Drawing on a qualitative-comparative approach grounded in document analysis, this study examines international HR instruments specifically Article 19 of the UDHR and ICCPR alongside Islamic normative sources comprising the Qur'an, Sunnah, fatwa council rulings, and maqasid al-shari'ah literature. Both systems recognize freedom of expression as a fundamental right, yet differ substantially in philosophical foundation. HR frameworks condition restrictions on the principles of legality, legitimate aim, necessity, and proportionality; Islamic Law, by contrast, frames expression as a moral trust bounded by the protection of maqasid al-shari'ah and the principle of amar ma'ruf nahi munkar. This tension produces concrete regulatory gaps in digital content moderation, particularly regarding hate speech, blasphemy, and disinformation. In response to these gaps, the study proposes a three-component integrative regulatory model: balanced cyber-regulation design, multi-stakeholder co-regulation mechanisms, and digital literacy grounded in cross-perspectival communication ethics. The model offers an operational framework for policymakers and digital platforms seeking to develop fair and contextually sensitive content moderation policies.